A Critical Voice on the Hajj by a Sumatran Pilgrim from the Early Twentieth Century - Suryadi, Suryadi; Lutfi, Mochtar; Ali, Moch.; Santoso, Listiyono; Firdaus, Rima (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
This paper examines a late 19th-century brochure entitled ‘Perdjalanan ke-‘Tanah-Tjoetji’ (A Pilgrimage to the ‘Holy Land’) written by Dja Edar Moeda, a Dutch-educated native teacher and a pioneer journalist and vernacular press entrepreneur in Sumatra. The text offers a critical perspective on the Hajj, differing from the majority of this corpus, which tends to show religious enthusiasm and saintly connotations. This paper demonstrates that the ‘deviant’ voice on the Hajj in the Brochure reflects the author’s concerns. As a native intellectual and religious modernist with a Western-secular education, he worries about the fate of his fellow native pilgrims, who are often victimised by rampant fraudulent practices in the organisation of the Hajj due to their illiteracy, map illiteracy, innocence, naivety and tendency to be submissive in their religious practice. In this respect, the Brochure indirectly criticises the Dutch East Indies colonial authority’s deficiencies in organising the pilgrimage and protecting the pilgrims as its colonial subjects.